Updating the Genome of the Elite Rice Variety Kongyu131 to Expand Its Ecological Adaptation Region - Wang, Rongsheng; Jiang, Guoqiang; Feng, Xiaomin; Nan, Jianzong; Zhang, Xiaohui; Yuan, Qingbo; Lin, Shaoyang (Frontiers in Plant Science, 2019)
As an elite rice variety cultivated in the third accumulative temperature zone in Heilongjiang Province, China, Kongyu131 has many excellent traits, such as high quality, high stability, early maturation and cold resistance. However, as with other crop varieties, Kongyu131 has regional restrictions, exhibiting decreased yields when grown at low latitudes. To address these problems, in this study, we crossed japonica and indica varieties and developed populations to detect related quantitative trait loci. We identified two populations that were segregated from normal plants, even at low latitudes. Therefore, we performed QTL analysis and started our study from these populations to expand the ecological adaptation region of Kongyu131. QTL analysis in a BC1F6 backcross inbred line population with 168 lines derived from a cross between Kongyu131 and GKMP showed a large pleiotropic QTL near 9 Mb on chromosome 7, which significantly delayed the HD of Kongyu131 and increased the plant height (PH), length of main panicle (LMP), number of primary branches (NPB) and grain number of main panicles (GNP). We also found a similar QTL in the population BC3F2 derived from Kongyu131 and GKLPL. Based on the QTL, we developed a gene module named CSQq7w9LPL with 5 single-nucleotide polymorphism (SNP) markers around the QTL. By backcrossing and monitoring with 197 SNP markers that were evenly distributed over 12 chromosomes, we obtained a new plant (a single point substitution line, SPSL) with a new Kongyu131 genome, carrying only a small chromosomal fragment less than 800 Kb from GKLPL. The background recovery ratio of the SPSL was 99.8%. Compared with Kongyu131, the SPSL exhibited a significant HD delay of approximately 31 days and increased PH, LMP and GNP values when planted in Jiamusi, Heilongjiang Province. The SPSL with the CSQq7w9LPL module, which delayed the HD of this variety significantly, could be moved south by more than 3 latitude units and cultivated in low-latitude regions. This study exemplifies the feasibility of expanding the regions of cultivation of elite rice varieties via similar methods.